PERSONS WITH DISABILITIES IN QUR’ANIC PERSPECTIVE: MAUDHUI STUDY OF TAFSIR AL-MUNIR: Penyandang Disabilitas Dalam Perspektif Al-Qur’an: Kajian Tafsir Maudhui Atas Tafsir Al-Munir - Ahmad Ajik Nur Fata Mubarok; Wildan Taufik (Tunas Harapan Ummat Foundation, 2026)
This article critically examines how disability is constructed through Qur’anic metaphors and mediated by contemporary Islamic interpretation, focusing on Wahbah az-Zuhaili’s Tafsir al-Munir. While Islamic discourse often emphasizes the Qur’an’s inclusivity toward persons with disabilities, such claims are frequently presented in normative and affirmative terms, leaving little room for critical engagement with the ethical implications of religious language. This study argues that the problem is not whether the Qur’an upholds human dignity, but how metaphorical uses of disability, such as blindness, deafness, and muteness, shape social perceptions and religious consciousness. Employing a thematic interpretation (tafsir maudhui) with a critical-analytical approach, this research analyzes key Qur’anic verses related to disability and examines how Tafsir al-Munir distinguishes between physical impairment and spiritual deficiency. The findings show that while az-Zuhaili consistently rejects theological stigmatization of physical disability, his interpretation largely reproduces classical metaphorical frameworks without sufficiently addressing their potential symbolic impact on contemporary disability ethics. This article contributes to Qur’anic studies by highlighting the ethical limits of moderate tafsir when confronting modern disability discourse. It proposes that Qur’anic inclusivity should not be understood merely as a moral assertion, but as an ongoing ethical project that requires critical evaluation of interpretive language and its social consequences.